Effect of zinc nutrition on economic productivity of rice (Oryza sativa) and soil biological properties - KUMAR, SANJEEV; SARANGTHEM, INDIRA; DEVI, N SURBALA; DEVI, K NANDINI; SINGH, N GOPIMOHAN (The Indian Journal of Agricultural Sciences, 2022)
Based on our findings, it can be concluded that application of Zn in transplanted rice is essential to harvest profitable yield under acidic soils of NEH region of India. Combined application (soil and foliar) was more effective instead of soil or foliar application alone. Successive yield increment of rice was noticed up to the application of Zn 7.5 kg/ha + foliar spray of Zn @0.5% at panicle initiation and booting stages. Thereafter productivity of rice slightly declined with increases of Zn doses in acidic soils. The application Zn @7.5 kg/ha + foliar spray of Zn @0.5% significantly improved yield attributing parameters of rice over control. Among the Zn nutrition treatments, application of Zn @7.5 kg/ha + foliar spray of Zn @0.5% registered 4.5% higher grain yield over its soil application. With regards to the soil biological properties successive increase of Zn doses improved the soil biological properties up to the application of Zn @10 kg/ha + foliar spray of Zn @0.5%. However, it remains statistically at par with Zn @7.5 kg/ha + foliar spray of Zn @0.5% at most of the growth stages of rice. Hence, application of Zn @7.5 kg/ha + foliar spray of Zn @0.5% at panicle initiation and booting stages is a profitable option for sustainable rice production in NEH, India besides sustaining the soil biological properties.